The Short-Run And Long-Run Relationship In The Indonesia Islamic Stock Returns - M Shabri Abd Majid (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This paper aims at empirically examining the short-run and long-run causal relationship between the Indonesian Islamic stock returns and selected macroeconomic variables namely inflation, money supply and exchange rate during the pre- and post- 2008 global financial turmoil period from 2002 until 2007 and from 2008 until 2013 by using monthly data. The methodology used in this study is time series econometric techniques i.e. the unit root test,co-integration test, error correction model (ECM) and variance decompositions(VDCs). The findings showed that there is cointegration between Islamic stock prices and macroeconomic variables. The results suggest that inflation, money supply, and exchange rate significantly affected the Islamic stock returns in Indonesia. These variables should be taken into account by the policy-makers as the important policy instruments in stabilizing Islamic stock markets in the countryDOI: 10.15408/aiq.v8i1.2505